(untitled) (Research, Society and Development, 2022)
The territorialization process is one of the steps developed by groups of professionals who are part of the Multiprofessional Residency in programs that work in Primary Care, used to contribute to the understanding of practical experiences in specialized mental health care in an ethical way, respecting the precepts of the SUS and raising awareness among those involved in the work process or a specific population. The present study aimed to identify the risks, vulnerabilities and potential of the territory covered by the NASF-AB II of the municipality of Camaragibe-PE, from April to May 2022, to support the intervention process in primary care for resident professionals in mental health. A qualitative observational research was carried out based on documentation and analysis of visits to the territory, interviews and biographical surveys. It was possible to have an overview of the main problems and potential of territory II in Camaragibe, where among the main problems are arboviruses, high rate of homicides and traffic accidents, and people affected by landslides and natural flood disasters. The negative points identified were the difficulty in carrying out health promotion and prevention actions and the fragility in the articulation between primary care and mental health networks. The extensive health, social, educational, cultural and leisure facilities are the territory’s potential. Finally, knowing the territory proved to be an indispensable task for a conscious and critical action of professionals working in it.